Peran Harga Diri Terhadap Kecenderungan Perilaku Self Injury Pada Remaja - Revangga Tito Saputro; Andik Matulessy; Nindia Pratitis (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine the relationship between self-esteem and the tendency of self-injury behavior in adolescents. This study uses correlational quantitative research. The sampling technique in this study used the incidental sampling method, subjects as many as 180 adolescents were taken from the entire population. Adolescents with domicile in the city of Surabaya became subjects in the study. The self-esteem scale and the tendency of self-injury behavior are two instruments that are owned in this study. Data analysis was carried out using product moment correlation analysis test with the help of SPSS version 20 for Windows. The correlation coefficient result is -0.298, showing if there is a negative relationship between the level of the research coefficient with a significant level of p = 0.000 < (p = 0.05). This shows that the higher the self-esteem, the lower the tendency of self-injury behavior, and vice versa, the lower the self-esteem, the higher the tendency of self-injury behavior.